PERAN AKADEMISI DALAM PEMBERIAN BANTUAN HUKUM BAGI MASYARAKAT KURANG MAMPU DI INDONESIA - Ridwan, Ridwan (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2012)
Every citizen of Indonesia, of course longing for a fast, simple and low cost judicial process. This may be done everyone has an access to justice without any exception. These conditions have been realized by the Constitutional Court decision that had to cancel Article 31 of Law Number 18 Year 2003 on Advocates, because the article is considered contrary to the Constitution of 1945 and has no binding legal force. However, the implementation of the Constitutional Court ruling will not necessarily be implemented, because in practice there are still debates among law enforcer (police, prosecutors, judges, lawyers) even academics about the legal standing of the law lecturer who perform service in the form of assistance to disadvantaged communities who are dealing with legal issues. This condition is caused by a lack of positive response to the Constitutional Court, and the lack of response is due to the lack of legal resources by extracting the part of law enforcement and academics for a growing source of law. Kata Kunci: Decision, Constitutional Court, law enforcer, academics, citizen , Justice.